Bat assemblage and its frugivorous diet in a Eucalyptus plantation - FÁBIO ANDRÉ F. JACOMASSA; VANESSA F.C. BORTOLOTTI; PEDRO HENRIQUE MIGUEL; MARCO AURÉLIO PIZO (Anais da Academia Brasileira de Ciências)
Abstract Habitat loss and fragmentation have enormous impacts on biodiversity and tree plantations can help alleviate these impacts. We study bat assemblage, as well as the diet of frugivorous bats in a managed Eucalyptus plantation of sustainable use in Rio Claro, São Paulo state, Brazil. We captured 86 bats of nine species, where five species of them ate 17 plant species, mostly pioneers (93.7%). Three species were most dominant, frequent and important in seed dispersal: seba’s short-tailed bat (Carollia perspicillata), great fruit-eating bat (Artibeus lituratus), and little yellow-shouldered bat (Sturnira lilium). These species are the most abundant and main seed dispersers in Brazil. Compared to literature data from other Eucalyptus plantations, we concluded that our studied Eucalyptus area with understory and emerging regenerating native species provided greater diversity than in areas where Eucalyptus is used commercially and the understory vegetation is constantly altered; the fruits exploited by these three bat species demonstrates their ability to adapt to food availability and coexist with other species; Eucalyptus forests cannot be considered as biological deserts if they are not managed so intensively as in commercial plantations.